The role of electrical and jasmonate signalling in the recognition of captured prey in the carnivorous sundew plant Drosera capensis - Krausko, Miroslav; Perutka, Zdeněk; Šebela, Marek; Šamajová, Olga; Šamaj, Jozef; Novák, Ondřej; Pavlovič, Andrej (The New phytologist, 2017)
The carnivorous sundew plant (Drosera capensis) captures prey using sticky tentacles. We investigated the tentacle and trap reactions in response to the electrical and jasmonate signalling evoked by different stimuli to reveal how carnivorous sundews recognize digestible captured prey in their traps. We measured the electrical signals, phytohormone concentration, enzyme activities and Chla fluorescence in response to mechanical stimulation, wounding or insect feeding in local and systemic traps. Seven new proteins in the digestive fluid were identified using mass spectrometry. Mechanical stimuli and live prey induced a fast, localized tentacle-bending reaction and enzyme secretion at the place of application. By contrast, repeated wounding induced a nonlocalized convulsive tentacle movement and enzyme secretion in local but also in distant systemic traps. These differences can be explained in terms of the electrical signal propagation and jasmonate accumulation, which also had a significant impact on the photosynthesis in the traps. The electrical signals generated in response to wounding could partially mimic a mechanical stimulation of struggling prey and might trigger a false alarm, confirming that the botanical carnivory and plant defence mechanisms are related. To trigger the full enzyme activity, the traps must detect chemical stimuli from the captured prey.
Keywords: electrical signal; action potential; Drosera; signální transdukce; Oxylipins; regulátory růstu rostlin; oxylipiny; enzymes; sundew; rostlinné proteiny; Models, Biological; carnivorous plant; Signal Transduction; fotochemické procesy; Photochemical Processes; biologické modely; Plant Growth Regulators; elektrofyziologické jevy; Photosystem II Protein Complex; Cyclopentanes; Electrophysiological Phenomena; cyklopentany; jasmonates; fotosystém II (proteinový komplex); long-distance signalling; Plant Proteins